(3GdCReGJ hGdeJZjQGJ GdEbJUGOjI hOhQ GdbWGY GdeUQaj (B/s - (3Ydj, CMeO TYHGf eMeOs ((3GdEScfOQjI(B: s (3ecJHI GdhaGA GdbGfhfjI(B, s, 2011)
(3GdCReGJ GdeGdjI (B" (3SQO JGQjNj (B"-(3GdQbGHI GdeUQajI Ydi GdbWGY GdeUQaj(B- (3GdeJZjQGJ GdEbJUGOjI GdeYGUQI hGdEbJUGO GdYGdej(B- (3GfYcGSGJ GdeJZjQGJ GdEbJUGOjI GdeYGUQI Ydi GdEbJUGO GdYGdej(B- (3GfYcGSGJ GdeJZjQGJ GdEbJUGOjI GdeYGUQI Ydi GdEbJUGOGJ GdfGejI (B- (3JWhjQ COGA GdHfc GdeQcRj hOhQg aj GdHdOGf GdfGejI (B- (3GdJhGab eY (B" (3HGRd(B2" (3hOhQ GdHfc GdeQcRj(B- (3JaYjd GdJYGhf Hjf GdHfhc GdeQcRjI aj GdHdOGf GdYQHjIs
Keywords: (3GdCReGJs; (3GdbWGY GdeUQajs; (3GdeJZjQGJ GdEbJUGOjIs